Digital Humanities and university extension in information science - Mendes, Edson Luiz; Minghelli, Marcelo (Advanced Notes in Information Science, 2023)
At the beginning of the twenty-first century, the understanding, effectiveness, and influence on society of issues related to information and its flow are increasingly sought, taking into account not only documents but also subjects, behaviors, and people, among others. Several areas of knowledge have given attention to this phenomenon due to its fast, instantaneous, and punctual social impact, favoring those with a greater understanding to use it according to their needs. Digital humanities, in dialogue with Information Science, are a transdisciplinary opportunity to contribute collectively and consciously to future generations, starting with the present in the face of past experiences, but without making the same mistakes, and also contribute, through ethics, respect and humanity, to the reduction of social inequalities using technological and digital tools. Thus, we dialogue with this study, presenting a possibility of practical action in Digital Humanities in the socially vulnerable community. Through university extension, the articulation between the academic community and the external community, through a relationship of equal rights and duties, promotes a cultural and scientific educational process, which, reaching awareness, allows the territory and society to be transformed and the academic world itself.